Perception, perceived scope, and potential barriers towards developing nurse practitioners cadre among health care providers and beneficiaries: A pilot study from Northern India - S Malar Kodi; Suresh K Sharma; Somprakas Basu (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The role of nurse practitioner (NP) emerged in early 1965 when general practitioners began working with nurses. Evidence across the world highlights the benefits achieved by the NP role. The Indian Nursing Council (INC) implemented a country-wide NP in critical care (NPCC) program with the approval of the ministry of health and family welfare (MoHFW) in 2017. The NP role is in its infancy in India. Hence, there is a need to assess the perception among beneficiaries and healthcare personnel. This study was conducted to assess the perception, perceived scope, and potential barriers for developing the role of NPs in India among beneficiaries and healthcare providers. MATERIAL AND METHODS: A descriptive, cross-sectional pilot study was conducted at AIIMS Rishikesh, Uttarakhand, India, among 205 participants (84 beneficiaries, 78 nurses, and 43 physicians) using a proportionate stratified random sampling technique. Likert scales and socio-demographic sheets were used to assess the perception, perceived scope of practice, and potential barriers in developing a NP cadre in India. Descriptive and inferential statistics were used for analyzing data. RESULTS: The mean age of beneficiaries was 37.98, nurses was 27.58, and physicians was 28.13 years, respectively. 121 (61%) of participants were highly favored, and 77 (38%) were in favor of developing NP cadre in India. They considered it to be necessary, feasible, and acceptable in India. The feasibility and necessity of the perception domain were highly significant (P < 0.001 and P < 0.003, respectively). Nurses (mean ± SD: 35.36 ± 3.55) considered that NPs could have a wide range of practice followed by beneficiaries (mean ± SD: 38.17 ± 3.68) than physicians (mean ± SD: 34.75 ± 5.95). Lack of awareness, the nonexistence of cadre structure, lack of acceptance of the role of physicians, and lack of clear policy were the key potential barriers to develop an NP cadre in India. CONCLUSIONS: In this study, participants had favorable views on employing NPs in India; thus, this role will improve healthcare access for beneficiaries. NPs can carry out a wide range of practices.However, a lack of awareness, no cadre structure, and a lack of a clear policy may hinder the development of the NP cadre in India.